2016
DOI: 10.1039/c5ob02513c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, radiolabeling with fluorine-18 and preliminary in vivo evaluation of a heparan sulphate mimetic as potent angiogenesis and heparanase inhibitor for cancer applications

Abstract: Heparan Sulfate (HS) mimetics are able to block crucial interactions of the components of the extracellular matrix in angiogenic processes and as such, represent a valuable class of original candidates for cancer therapy. Here we first report the synthesis and in vitro angiogenic inhibition properties of a conjugated, novel and rationally-designed octasaccharide-based HS mimetic. We also herein report its labeling with fluorine-18 and present the preliminary in vivo Positron Emission Tomography imaging data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Dollé and coworkers synthesized an octasaccharide heparin mimetic that interfered with the process of angiogenesis and metastasis [102]. It potently inhibited heparanase, FGF2, VEGF, SDF-1α, PDGF-β, and cell proliferation in vitro and is being tested in vivo in animal models.…”
Section: Gag Mimeticsmentioning
confidence: 99%
“…Dollé and coworkers synthesized an octasaccharide heparin mimetic that interfered with the process of angiogenesis and metastasis [102]. It potently inhibited heparanase, FGF2, VEGF, SDF-1α, PDGF-β, and cell proliferation in vitro and is being tested in vivo in animal models.…”
Section: Gag Mimeticsmentioning
confidence: 99%
“…Karoli et al demonstrated that carbohydrate-based HS-mimicking compounds, PI-88 and analogues, inhibit heparanase and compete with growth factors (FGF-1, FGF-2, and VEGF) for binding to HS, and therefore impact anti-angiogenic and anti-metastatic activity [48,181]. Another octasaccharide-based heparin mimetic synthesized by Dollé and coworkers was characterized in vitro for its binding affinities and towards VEGF-A, FGF-2, PDGF-β, and SDF1-α using the BIAcore technology and for the potential inhibition in an heparanase activity assay [182]. This novel molecule could thus potentially inhibit angiogenesis by interfering with components of the extracellular matrix.…”
Section: Targeting the Tumor Microenvironmentmentioning
confidence: 99%
“…Kuhnast et al [ 241 ] reported the in vitro antiangiogenic properties of a rationally designed octasaccharide-based HS mimetic and of its fluoropyridinilated radioactive derivative. The parental oligosaccharide showed strong affinity for VEGF-A, FGF2, PDGF-β, and SDF-1α, as well as potent heparanase inhibitory activity.…”
Section: New Molecules and Perspectivesmentioning
confidence: 99%